Understanding the origins of remote asymmetric induction in the boron aldol reactions of beta-alkoxy methyl ketones. - Paton, R; Goodman, J (2006)
We report theoretical studies into the remote 1,5-stereoinduction shown by certain types of beta-alkoxy methyl ketones in boron-mediated aldol reactions with achiral aldehydes. For a range of common alkoxy groups, our calculations are in excellent agreement with experimentally observed diastereoselectivities. In the aldol transition structures, a stabilizing hydrogen bond between the alkoxy oxygen and formyl proton leads to preferential formation of the 1,5-adduct, by minimizing steric interactions between the beta-alkyl group and one of the ligands on boron.